Eating out intensity, ultra-processed foods and BMI among Albanian youth - Ferenc Vincze; Taulant Muka; Fabian Eichelmann; Erand Llanaj (Cambridge University Press, 2023)
Abstract Objective: Ultra-processed foods (UPF) and eating out of home (OH) are changing nutrition, particularly among youth in constrained settings. We aimed to assess the role of eating OH intensity on the associations of UPF and unprocessed or minimally processed foods (UMPF) with BMI among Albanian youth. Design: Cross-sectional. Setting: Albania, a south-eastern European country. Participants: 281 youth, predominantly females. Methods: UPF and UMPF were defined based on NOVA, while eating OH intensity based on energy percentage from OH foods. Multivariable models tested associations of UPF and UMPF with BMI stratified by eating OH intensity, controlled for relevant covariates including diet quality, portion size and costs. Results: The respondents age ranged between 18 and 23 years with a female predominance (87·5 %). Mean energy from UPF and UMPF was 846 (sd: 573·0) and 802·9 (422·5) kcals, respectively. Among substantial at home eaters UPF intake was not associated (β = −0·07, 95 % CI (−0·13, 0·267)) with BMI; however, UMPF negatively associated with BMI (β = −0·24, 95 % CI (−0·43, −0·06)). Among those defined as substantial OH eaters, UPF (β = 0·24, 95 % CI (0·08, 0·40)) and UMPF (β = 0·18, 95 % CI (0·04, 0·33)) were positively associated with BMI. Conclusions: Our findings provide evidence for the hypothesis that eating OH plays an important role in the association of UPF and UMPF with BMI in youth. While causality cannot be established due to cross-sectional design, to the best of our knowledge, we provide the first assessment of UPF and UMPF intake in a south-eastern European setting, while highlighting the need for establishing and integrating youth nutrition into national nutritional surveillance systems for key dietary risk factors in Albania.